Polygamy and law in Northern Nigeria : a case study of its practice and impact on women's right in Bauchi State - Yelwa, Mansur Isa (Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, 2014)
The current Shari'ah legal framework as administered in Northern Nigeria has been in existence since long period of its ancient history. It went through distinct dimensions throughout the chronicles of its legal aggregate, starting from the pre colonial era, via the colonial epoch, up to the post independence eon. Buttressed by this Shari'ah framework, polygamy remains a crucial issue of Islamic family law, owing to its ample practice in Nigeria. Religion and culture are the main reasons behind its overwhelming acceptability and widespread. The religious background on polygamy undoubtedly correlated with the cultural position of the Nigerian people, thereby significantly influencing its practice. Besides overheating the controversies surrounding the practice, it is rightly argued that the mix-up of religion and culture rendered the practice inconsistent with the religious principles and its objectives in polygamy. This phenomenon posited the Nigerian framework incompatible with the contemporary developments in the legal framework of polygamous practices around the Muslim world. The main remonstrance surrounding the inconsistent practice is its pessimistic impact on the rights of women which Islamic law overwhelmingly protects. The Nigerian Shari'ah framework with respect to family law generally, and on polygamy in particular, is mainly based on uncodified and unregulated classical law of the Maliki School. The non codified system is seen as an efficacious factor responsible for numerous socio-legal botherations linked to polygamous practice in Nigeria. This thesis lucubrates the practice of polygamy in Nigeria and how it affects the rights of women in the Northern Nigerian states. It presents an in-depth study of the classical Maliki law and to what extent is the Nigerian practice compatible with the law. The methodology employed the library-based doctrinal research approach as well as both quantitative and qualitative empirical research approach. Bauchi state was coherently selected as a model of case study for empirical research about the practice of polygamy in Northern Nigeria. For the purpose of presenting a comparative overview of model jurisdictions, the thesis canvasses upon a concise but comprehensive appraisal of the legal framework and practice of polygamy in selected Muslim countries. It concludes with a sum-up of the thesis and a recapitulation of its salient findings and sets forth the author's suggestions. The research is aimed at proposing for the review and gradual reform in the administration of Islamic family law for an arrayed and improved Shari'ah implementation in Bauchi state and Nigeria at large.